Development of Boxing Sports Samsak for Novice Athletes - Lamkasea Bancin; Samsuddin Siregar (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. This study aims to determine the feasibility of developing laseaban bags in boxing. Materials and methods. The research sample was 30 athletes. The feasibility of the bag is first validated by experts, namely equipment experts, material experts (boxing coaches), and sports experts. Furthermore, small group tests and large group tests are tested on athletes. Results. In a large group test with a total of 20 (twenty) athletes with 3 (aspects) with an indicator of the suitability of the bag with the comfort of using the bag, an indicator of implementation, and an indicator of user interest with 10 (ten) questions. With an average score of 4.35 with a percentage of 97.00% in the very good category. Conclusions. The following is a response to the interest of athletes when using or using a tool developed by the researcher, namely the laseaban bag.